SISTEM PRODUKSI TERDISTRIBUSI MANDIRI: PERANGKAT LUNAK INTI PENGEMBANGAN SISTEM PRODUKSI - Yatna Yuwana Martawirya; Rochmad Setyadi (Mesin, 2000)
The objective of the present research is to develop an application software called MSC (Manufacturing System Core) which is used as a core in the development of a manufacturing system software. The development of MSC is based on ADiMS (A utonomous Distributed Manuï¬zcturing System). An object-oriented modeling method is adopted to represent the autonomous component of the manufacturing systems. The example of minimum application of MSC and the method of extent are discussed to understand the modularity of MSC. Software development technology applied at MSC are discussed to see the ability of MSC in the data sharing with other application.